Propuesta de un plan de marketing para la empresa SEGAL CIA. LTDA. de la ciudad de Loja - Rodríguez Fernández, Paola Carolina (2019)
The work focuses on developing a marketing plan for the private security company SEGAL Cía. Ltda., Created on October 19, 1992 with the corporate purpose of providing advisory, surveillance and private security services to companies of financial activities of the public and private sector, domiciles and commercial enterprises; It is located in the southern sector of the city of Loja, in the neighborhood El Electricista Pedro Vicente Maldonado and Tomas Alba streets. SEGAL CIA LTDA., Is governed by the security and surveillance law issued in July 2008 the same that due to the vertiginous technological advance was forced to be updated in the month of August 2014 allowing to find the best performance of private security and surveillance companies to cover the deficit that exists in the public force, in relation to the fight against crime endorsed by the Ministry of Interior and the Joint Command of the armed forces. In the development of this thesis, the execution of a marketing plan is proposed that allows to make a proposal to a better performance of its services, in order to achieve market positioning and obtain greater profitability, for its development it has the opening of the manager of the company Mayor Luis Araujo who helped us with the necessary information to develop it. The thesis project begins with a summary, where each phase of the thesis is detailed in a very general way making importance in the results obtained, then the investigated problem is contextualized and an analysis in summary form, the most important aspects of the research work All this is part of the introduction. Then we have the review that is the conceptual support that has been applied throughout the development of the proposal. Next we have the materials and methods, where the materials used in the development of the research are revealed, as well as the use of methods such as: descriptive inductive method, deductive method, statistical method, analytical method and the implementation of techniques such as the survey aimed at the only client currently Banco de Loja, its staff 57 collaborators (52 guards including console operators and 5 admirals, and the interview addressed to the manager. The results are shown below, in which a situational diagnosis of the company “SEGAL CIA LTDA” is made in the first instance, which is related to the company's environment and through which a light analysis of the situation can be made current and historical company in a way that allows me to get even more familiar with its surroundings Then we perform an analysis of the external factors (political, economic, social, technological and competition) and Porter's 5 forces, which could influence in some cases as threats and opportunities for the company. From this it could be determined that the EFE matrix whose result was 2.56 which indicates that the company is taking advantage of the opportunities and minimizing the threats. Likewise, an analysis of internal factors was carried out which can influence as weaknesses or strengths for SEGAL CIA LTDA and when analyzing the EFI matrix it could be evidenced that once these factors have been defined, the weighted value is 2.47 indicating that the company has Weaknesses that can affect the company therefore the opportunities must be seized and through it the weaknesses must be eliminated. With the results of the EFE and EFI matrix, the SWOT matrix was built as one of the specific objectives set out in the project, which allowed the consolidation of strengths, weaknesses, opportunities and threats, and should be the strengthened strengths and opportunities exploited. After the SWOT matrix, it allowed me to propose the high impact matrix in which the strategies for the proposal were elaborated. From the high impact matrix the four marketing objectives are determined which are: Search for new market segments to boost the positioning of the company whose budget outlook is $ 200.00; Acquire new technologies to offer a new and modern service in order to set up a monitoring console whose budget is planned at $ 12,250.00; Implement an advertising campaign to attract new customers who know the company and are interested in their services 960.00 budget; Establish an additional service plan in each of the contracts acquired by customers, whose prediction of expenditure will be $ 2,000.00. Among the most important conclusions of the company we find that the lack of a marketing plan prevents its development and corporate growth, therefore its services do not reach the entire current market. To comply with the Marketing Plan, the company requires investing $ 15,410.00; This investment will allow the company to implement the study proposed and to achieve a strong position in the current market. Finally, my suggestion is to implement and implement the proposed marketing plan in order to improve the current situation of the company SEGAL CIA LTDA, likewise it is recommended that managers socialize this document and perform the respective evaluation and control of the areas involved to verify that the objectives set are executed in order to increase your income and become an optimal services company